2021
DOI: 10.1039/d0ee02984j
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing accuracy and efficacy in data-driven materials discovery for the solar production of hydrogen

Abstract: The production of hydrogen fuels, via water splitting, is of practical relevance for meeting global energy needs and mitigating the environmental consequences of fossil-fuel-based transportation. Water photoelectrolysis has been proposed...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 102 publications
3
41
0
Order By: Relevance
“…Moreover, this work shows that DFT+U with Hubbard parameters determined nonempirically can be used to predict reliable band gaps at lower computational cost than that of hybrid functionals (such as HSE06 [96,97]) that are popular for predicting band gap values. This is important for high-throughput studies that require efficient and reliable estimates of the band gaps at moderate computational cost for various technologically relevant materials such as photocatalysts [98,99], solar cells [100,101], and transparent conductors [102].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this work shows that DFT+U with Hubbard parameters determined nonempirically can be used to predict reliable band gaps at lower computational cost than that of hybrid functionals (such as HSE06 [96,97]) that are popular for predicting band gap values. This is important for high-throughput studies that require efficient and reliable estimates of the band gaps at moderate computational cost for various technologically relevant materials such as photocatalysts [98,99], solar cells [100,101], and transparent conductors [102].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic mail: vxg8@psu.edu cial applications 15 . Data driven prediction of new photocatalytic materials provides new opportunities for expediting the discovery and development of efficient photocatalysis 16 . Most of the reported photocatalysts require co-catalysts, sensitizers or support materials to reach above 0.1 µmol/h hydrogen production rate 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This motivates our present work in building an ultra-sensitive tool for detecting small rates of hydrogen generation. Using this tool, we study the hydrogen evolution rates of two recently identified photocatalyst materials 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations were very useful to conduct e.g. a DFT+U -based high-throughput search of novel materials for the photocatalytic water splitting [90]. In the current work, we go further and explore the accuracy of the extended DFT+U +V formulation for predicting band gaps and its sensitivity to the type of Hubbard projectors.…”
Section: Key Question Ismentioning
confidence: 90%